2012
DOI: 10.1590/s0102-67202012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Frequência e fatores preditivos relacionados a metástase linfática em câncer gástrico precoce

Abstract: Ulceration, lesions larger than 50 mm, infiltration of the submucosal layer and lymphatic invasion are independent risk factors related to lymphatic metastasis in early gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Multiple Cox regression analysis showed that only N staging could independently predict the prognosis of EGC patients. Inconsistent with previous studies [ 18 ], we found that N staging was the only independent prognostic factor and that tumor size, tumor cell differentiation and depth of tumor infiltration could not independently predict EGC patient prognosis. The four above-mentioned clinicopathological factors correlated with LNM and therefore could not directly predict EGC prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…Multiple Cox regression analysis showed that only N staging could independently predict the prognosis of EGC patients. Inconsistent with previous studies [ 18 ], we found that N staging was the only independent prognostic factor and that tumor size, tumor cell differentiation and depth of tumor infiltration could not independently predict EGC patient prognosis. The four above-mentioned clinicopathological factors correlated with LNM and therefore could not directly predict EGC prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…The ulcers induced in the present study were large in diameter and deeply penetrated into the muscular layer. According to some authors, the large size of gastric ulcer was closely related with difficulties in its treatment [ 3 ], the likelihood of ulcer malignancy [ 6 , 46 , 4 ] and lymph node metastasis [ 5 , 47 ]. Extensive, deeply penetrating ulcers destroy deeper tissues of the gastric wall, including nerve pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng’s group [ 39 ] reported that the five- and ten-year survival rates were significantly lower in patients with lymph node metastases which are low-frequency events (2.6–4.6% of mucosal cancers) in early gastric cancer with mucosal invasion [ 16 , 40 ]. However, the incidence of lymph node metastasis in submucosal cancers has been reported as approximately 20% [ 41 , 42 ]. The submucosa is divided into 3 layers: SM1, SM2, and SM3 according to their depth and some reports indicate that these metastases began in the SM3 layer [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%